2014
DOI: 10.1093/cercor/bhu259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beta-Amyloid on Resting State Functional Connectivity Within and Between Networks Reflect Known Patterns of Regional Vulnerability

Abstract: Beta-amyloid (Aβ) deposition is one of the hallmarks of Alzheimer's disease (AD). However, it is also present in some cognitively normal elderly adults and may represent a preclinical disease state. While AD patients exhibit disrupted functional connectivity (FC) both within and between resting-state networks, studies of preclinical cases have focused primarily on the default mode network (DMN). The extent to which Aβ-related effects occur outside of the DMN and between networks remains unclear. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 93 publications
20
90
0
Order By: Relevance
“…Temporal cortex and entorhinal cortex of mice were chosen as representative region. These two regions were selected because early pathological features of AD were mainly found in the temporal lobe and in entorhinal cortex [15,16]. Consistent with previous data [17,18], we also observed that sirt3 was ubiquitous localized in the nuclear and cytoplasm.…”
Section: Expression Of Sirt3 In the App/ps1 Double Transgenic Micesupporting
confidence: 86%
“…Temporal cortex and entorhinal cortex of mice were chosen as representative region. These two regions were selected because early pathological features of AD were mainly found in the temporal lobe and in entorhinal cortex [15,16]. Consistent with previous data [17,18], we also observed that sirt3 was ubiquitous localized in the nuclear and cytoplasm.…”
Section: Expression Of Sirt3 In the App/ps1 Double Transgenic Micesupporting
confidence: 86%
“…9 For instance, it has repeatedly been demonstrated in PiB-PET studies that the presence of amyloid plaques is sufficient for there to be functional connectivity changes not only in the DMN, 10 but also in the SAL and ECN 32 and even between networks. 33 In the present study, we found that a lower level of CSF Aβ 1-42 was associated with decreased functional connectivity between the ventral DMN and the LN and between the ventral DMN and the anterior SAL in patients with Alzheimer disease, whereas in patients with aMCI there was stronger functional connectivity between some regions of the ventral DMN and the VSN/DAN and decreased connectivity between other regions of the ventral DMN and the VSN/ DAN. Amyloid burden in the DMN areas is a plausible explanation for the functional connectivity disruption between these RSNs; in addition, previous studies using PiB-PET amyloid imaging have demonstrated that amyloid accumulation occurs throughout the lateral frontoparietal cortex 34 and extends to the attention network, 35 affecting the functional connectivity of regions belonging to the VSN/DAN in patients with Alzheimer disease.…”
Section: Discussionsupporting
confidence: 53%
“…DMN hypoconnectivity may arise as early as middle age [43,44], with decreases occurring at differing rates between sexes [45] most likely due to the differential effect of sex on AD risk [46]. Reduced DMN integrity has also been reported in cognitively normal elderly with abnormal levels of CSF amyloid or tau proteins [47], as well as PET-detectable cerebral amyloidosis [48]. These results suggest that some of the effects related to normal aging in the literature may be driven by preclinical AD.…”
Section: Cognitively Normal Elderly At Risk For Loadmentioning
confidence: 99%